Mediation and conciliation: what is the best option? - Targino Trede, Rosilmar; Augusto de Oliveira Rangel, Leonardo (Seven Editora, 2023)
This work aimed to study the mediation and conciliation contained in the legislation in force as well as in the relevant doctrine, presenting the existing differences and similarities. It will address the functions of mediators and conciliators, when exercising their attributions. At the end, it signals which of the conflict resolution modalities - mediation or conciliation - are suitable for conflict resolution. The research method used was bibliographic consultation and legislation.